Development of Robust Metal‐Supported SOFCs and Stack Components in EU METSAPP Consortium1. Issue 4 (8th May 2017) - Sudireddy, B. R.; Nielsen, J.; Persson, Å. H.; Thydén, K.; Brodersen, K.; Ramousse, S.; Neagu, D.; Stefan, E.; Irvine, J. T. S.; Geisler, H.; Weber, A.; Reiss, G.; et al.
Abstract: The potential of MS‐SOFCs was demonstrated through the previous EU METSOFC project, which concluded that the development of oxidation resistant novel metal‐supported solid oxide fule cell (MS‐SOFC) design and stack is the requirement to advance this technology to the next level. The following EU METSAPP project has been executed with an overall aim of developing advanced metal‐supported cells and stacks based on a robust, reliable and up‐scalable technology. During the project, oxidation resistant nanostructured anodes based on modified SrTiO3 were developed and integrated into MS‐SOFCs to enhance their robustness. In addition, the manufacturing of metal‐supported cells with different geometries, scalability of the manufacturing process was demonstrated and more than 200 cells with an area of ∼150 cm 2 were produced. The electrochemical performance of different cell generations was evaluated and best performance and stability combination was observed with doped SrTiO3 based anode designs. Furthermore, numerical models to understand the corrosion behavior of the MS‐SOFCs were developed and validated. Finally, the cost effective concept of coated metal interconnects was developed, which resulted in 90% reduction in Cr evaporation, three times lower Cr2 O3 scale thickness and increased lifetime. The possibility of assembling these cells into two radically different stack designs was demonstrated.